Identifying customer needs for electric bicycle product design using the Kano model and Quality Function Deployment (QFD) - Sahrupi, Sahrupi; Dzulkifli, Dzulkifli; Rosihin, Rosihin (Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to identify user preferences regarding product quality, specifically in the design of electric bicycles. The study was conducted using the Kano Model and Quality Function Deployment approaches. The research process began with identifying customer complaints about electric bicycle quality, followed by a literature review, designing research instruments, determining the target segment of electric bicycle users, collecting and processing data, and designing geometric representations of the product. The results identified seven attributes classified under the Attractive category in the Kano Model. Based on the House of Quality analysis and consumer needs, several recommendations were made to enhance product quality. The proposed design improvements include adding turn signals to the front and rear, designing a radius-shaped backrest with specific dimensions, implementing an adjustable height lever, creating social media advertisements and collaborating with public figures, modifying handlebars for better ergonomics, offering metallic and matte color options, and increasing battery capacity from 12 Ah to 20 Ah. These findings contribute to the development of electric bicycles that better meet consumer expectations and enhance user satisfaction.